Identificación de jóvenes talentos en fútbol: características condicionales, antropométricas y fisiológicas como predictores del rendimiento - Bidaurrazaga-Letona, I.; Lekue, J. A.; Amado, M.; Santos-Concejero, J.; Gil, S. M. (Revista Internacional de Ciencias del Deporte, 2015)
The aim of this study was to provide a complete profile of elite young soccer players. Fifty-five players of the Under-14 category of Athletic Club Bilbao participated in this study. Players were classified into 4 playing positions: forwards (n=30), midfielders (n=15), defenders (n=37) and goalkeepers (n=15). Complete anthropometry, chronological age (CA), age at peak height velocity, 15-m sprint test, agility test, Yo-Yo IT level 1 (Yo-Yo IR1), counter-movement jump and hand dynamometry were measured. Results were transformed into z-scores and summed up to make two performance composites (SCORE and SCOREHG). One-way analysis of variance and a Bonferroni post-hoc test were used to examine the differences between playing positions. Multiple linear regression analysis was performed to estimate the contribution of independent variables to performance indicators. The level of significance was set at P<0.05. Significant differences were observed between playing positions in body mass and height (P<0.05); CA, maturity offset and muscle % (P<0.01); sum of skinfolds, fat %, endomorphy, sprint and agility tests (P<0.001). Stepwise regression analysis revealed that CA and sum of skinfolds were the most important predictors of performance. Collectively, playing positions were characterised by specific anthropometrical characteristics whereas no significant positional differences were observed in performance. This study provides further insight concerning coaches` practice of selecting young soccer players because of anthropometrical characteristics rather than for performance advantages.